THE EFFECT OF JIGSAW TECHNIQUE ON THE READING ABILITY OF THE FIRST YEAR STUDENTS OF MTsN 3 BENGKALIS IN DESCRIPTIVE TEXTS - Juli, Kurnia Purnama; azhar, Fadly; Aruan, Rumiri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : The objective of this research was to find out whether or not there is a significant effect of jigsaw technique on the reading ability of the first year students of MTsN 3 Bengkalis in descriptive texts.This is a pre-experimental research with one group pre-test and post-test design. In conducting this research, a single group conducting of 25 students was selected through cluster random sampling as the sample of the research. This research used reading test consisted of 40 items.Research findings should that, the mean score of pre-test was 58.20 and the mean score of post-test was 68.80. The result also showed that the value of t-test (8.228) is higher than t-table (2.064) at the significance level 5%. It means that Alternative Hypothesis (Ha) was accepted and Null Hypothesis (Ho) was rejected. Hence, there is a significant effect of jigsaw technique on the reading ability of the first year students of MTsN 3 Bengkalis in descriptive text.Key Words: Effect, Jigsaw Technique, Reading Ability, Descriptive Text